2017
DOI: 10.1037/hea0000420
|View full text |Cite
|
Sign up to set email alerts
|

An online skin cancer risk-reduction intervention for young adults: Mechanisms of effects.

Abstract: Objective The study’s purpose was to investigate moderator, implementation, and mediator variables related to the efficacy of UV4.me, an internet intervention that decreased ultraviolet radiation (UV) exposure and increased skin protection behaviors among young adults. Methods Nine-hundred sixty-five 18-25 year olds at risk for skin cancer were recruited nationally online. Participants were randomized to an experimental website (UV4.me), a control website, or assessment only. Participant characteristics (mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
(106 reference statements)
0
18
0
1
Order By: Relevance
“…Fourteen studies (Chait et al . ; Cooper, Goldenberg, & Arndt, ; Cornelis et al ., ; Heckman, Handorf, Darlow, Ritterband, & Manne, ; Hevey et al ., ; Hillhouse et al ., , ; Jackson & Aiken, ; Mahler, Beckerley, et al ., ; Mahler, Kulik, et al ., ; Owen et al ., ; Stapleton et al ., , ; Williams et al., ) examined the effectiveness of interventions not classed as either of the above on a combination of all of the outcome variables, as well as sun protection intentions, UV exposure, and UV exposure intentions separately. For the effects of these interventions on the above outcome variables, the combined effect size was small, r + = .191; k = 14, N = 3,895, 95% CI = 0.117–0.265, p < .001.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies (Chait et al . ; Cooper, Goldenberg, & Arndt, ; Cornelis et al ., ; Heckman, Handorf, Darlow, Ritterband, & Manne, ; Hevey et al ., ; Hillhouse et al ., , ; Jackson & Aiken, ; Mahler, Beckerley, et al ., ; Mahler, Kulik, et al ., ; Owen et al ., ; Stapleton et al ., , ; Williams et al., ) examined the effectiveness of interventions not classed as either of the above on a combination of all of the outcome variables, as well as sun protection intentions, UV exposure, and UV exposure intentions separately. For the effects of these interventions on the above outcome variables, the combined effect size was small, r + = .191; k = 14, N = 3,895, 95% CI = 0.117–0.265, p < .001.…”
Section: Resultsmentioning
confidence: 99%
“…Self-reported intervention adherence varied for each of the three intervention components. Adherence to the presentation (92%) and the booklet (68%) is higher in comparison to a study that reported that less than half of online skin cancer risk-reduction modules were completed by young people (18-25 years) [54]. The study found that the intervention was more effective in young people who completed more of the modules, thus highlighting the importance of adherence [55].…”
Section: Discussionmentioning
confidence: 55%
“…Self-reported intervention adherence varied for each of the three intervention components. Adherence to the presentation (92%) and the booklet (68%) is higher in comparison to a study that reported that less than half of online skin cancer risk-reduction modules were completed by young people (18-25 years) [55]. The study found that the intervention was more effective in young people who completed more of the modules, thus highlighting the importance of adherence [56].…”
Section: Discussionmentioning
confidence: 55%